2017
DOI: 10.22271/ortho.2017.v3.i3g.74
|View full text |Cite
|
Sign up to set email alerts
|

Role of teriparatide in fracture healing: A prospective study

Abstract: Background: Proximal Femoral Nail (PFN) provides tangible evidence for its usage in unstable pertrochanteric fractures. There are a veritable number of references which show that PFN by virtue of its intramedullary fixation reduces the tensile strain thereby mitigating implant failure. Ours is a prospective study done on 50 subjects to assess the outcome of PFN usage in unstable pertrochanteric fractures. Methodology: 50 patients with Jensen Michaelsen type III, IV, V intertrochanteric and reverse oblique frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The duration of treatment varied between two to four months, depending on the type of fracture and the time required for radiographic evidence of union. The study found that fractures treated with 20 µg of teriparatide showed early signs of union with significant callus formation, a decrease in the time required for radiographic union, and early rehabilitation of patients in all three groups [36].…”
Section: Case Reports and Seriesmentioning
confidence: 90%
See 1 more Smart Citation
“…The duration of treatment varied between two to four months, depending on the type of fracture and the time required for radiographic evidence of union. The study found that fractures treated with 20 µg of teriparatide showed early signs of union with significant callus formation, a decrease in the time required for radiographic union, and early rehabilitation of patients in all three groups [36].…”
Section: Case Reports and Seriesmentioning
confidence: 90%
“…A prospective study done by Saraf et al showed a positive result. The study found that for delayed union fractures, the use of teriparatide was associated with a shorter healing time compared to the group treated with a placebo [36]. Another prospective study done by Kastirr et al also showed a positive result after an average of 4.1 ± 1.5 (two to six) months after PTH treatment.…”
Section: Prospective Studiesmentioning
confidence: 91%
“…Treatment of non-union fractures using teriparatide helps patients to avoid undergoing another surgical procedure and problems associated with auto-grafts such as injury or pain to donor site or neurovascular damage [12]. Side effects include -nausea, headache, and vomiting.…”
Section: Dudhia and Mahajanmentioning
confidence: 99%
“…Local side effects at site of injection include -pain, itching, swelling, and erythema. It can also cause an increase in serum levels of uric acid; hence, it should be prescribed with caution in patients with renal disease impairment [12].…”
Section: Dudhia and Mahajanmentioning
confidence: 99%
See 1 more Smart Citation